PENGENALAN KEMAMPUAN MENGGAMBARKAN RANGKAIAN KEJADIAN MASA LAMPAU MELALUI PEMBELAJARAN BAHASA INGGRIS DI POLITEKNIK KESEHATAN JAYAPURA - Monika Gultom; Afner Saut Sinaga (JURNAL PENGABDIAN PAPUA, 2023)
This community service activity aims to introduce the ability to describe a series of past events through learning English at the Department of Medical Laboratory Medic of Jayapura Health Polytechnic in order to develop their ability to write and explain a series of events that have occurred previously in English well by developing their creativity and previous experience in communicating with other people. Specifically, this activity introduces how to develop students' thinking abilities and creativity using previous experience and knowledge as well as communicating in English orally as one of the assets that are needed by a reliable medical laboratory in the future. Jayapura Health Polytechnic (Poltekes Jayapura) is an institution that operates in two strategic fields, namely education, and health. Altogether in the field of education and health, they will produce prospective medical workers who are currently very much needed by the community in terms of laboratory test examinations regarding the pandemic and endemic era and also international needs that require not only lab skills but also foreign language skills in English that are qualified. This service activity also aims to introduce the importance of exploring and exploring previous/past knowledge and experiences and utilizing motivating and inspiring others in solving various problems that will be faced by each individual in everyday life. This activity was carried out approximately three times with material on the language rules needed to describe the events of the light period in English, surveys of the location of service implementation, implementation of community service, and seminars on community service results. This activity showed that the students of the Technical Laboratory Medic (TLM) Department of Poltekes Jayapura realized the importance of having the ability to describe a series of past events in English, and students became more skilled in describing past events in English. In addition, students of the TLM Department of Poltekes Jayapura are interested in developing themselves, especially in reading and writing a series of past events properly and correctly, and becoming more confident in their use in describing the final series of events in English.Keywords: learning English; student; describe; language; skill in describing